2010
DOI: 10.1080/15379418.2010.512233
|View full text |Cite
|
Sign up to set email alerts
|

Factors to Explore in Doing Child Custody Evaluations Involving Gay and Lesbian Parents

Abstract: Objective: The number of homosexual parents in the United States involved in child custody cases is growing. Current recommendations suggest that parents' sexual orientation should not impact these evaluations. This review examines the supporting literature and reports the findings in a useable way for evaluators. Method: The author thoroughly searched the literature using several keywords and databases. Results: Fifteen studies were included. The literature suggested no detrimental impact; however, limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Recent studies identified specific, unmet and unique needs for LGBTQ individuals in residential substance abuse treatment (Cochran & Cauce, 2006;Cullen, Courbasson, Quintero, Myslik, & Guimond, 2010) as well as regarding employment discrimination (Gates, 2010) and gerontological social work (Almack, Seymour, & Bellamy, 2010;Bell, Bern-Klug, Kramer, & Saunders, 2010;Kuyper & Fokkema, 2010;Stein, Beckerman & Sherman, 2010). Further examples of this trend include the need to incorporate and address unique issues arising in child custody evaluations when one or more parents are lesbians or gay men (Raley, 2010), the need for appropriate provision of health care services to LGBTQ adolescents (Kitts, 2010), and the need to ensure high-quality treatment for lesbians who were victims of intimate partner violence (Oswald, Fonseca, & Hardesty, 2010).…”
Section: Tentative Implications For Social Work Educationmentioning
confidence: 94%
“…Recent studies identified specific, unmet and unique needs for LGBTQ individuals in residential substance abuse treatment (Cochran & Cauce, 2006;Cullen, Courbasson, Quintero, Myslik, & Guimond, 2010) as well as regarding employment discrimination (Gates, 2010) and gerontological social work (Almack, Seymour, & Bellamy, 2010;Bell, Bern-Klug, Kramer, & Saunders, 2010;Kuyper & Fokkema, 2010;Stein, Beckerman & Sherman, 2010). Further examples of this trend include the need to incorporate and address unique issues arising in child custody evaluations when one or more parents are lesbians or gay men (Raley, 2010), the need for appropriate provision of health care services to LGBTQ adolescents (Kitts, 2010), and the need to ensure high-quality treatment for lesbians who were victims of intimate partner violence (Oswald, Fonseca, & Hardesty, 2010).…”
Section: Tentative Implications For Social Work Educationmentioning
confidence: 94%
“…Finally, the evidence has suggested that children of gay and lesbian parents are generally as well-adjusted as children of heterosexual parents (Biblarz & Savci, 2010;Patterson, 2005;Raley, 2010). They report positive peer relationships (Golombok et al, 1983;Golombok et al, 1997;Green, 1978;Green et al, 1986;Patterson, 1994), and may even experience a greater sense of connection to school peers than do children of heterosexual parents (Wainright & Patterson, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Goldberg (2010, p. 169) has also acknowledged a concern with self-presentation bias by parents, as well as has Raley (2010, p. 188). Gartrell et al.…”
Section: Looking Deeper Into the Researchmentioning
confidence: 99%